Assessment of Barrier and Selection of Strategies for Loading and Unloading Operations at Ports using Fuzzy BWM-MABAC - Salsabila, Nadhea Aurelie; Utama, Dana Marsetiya (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study developed an integrated Fuzzy Multi-Criteria Decision Making (MCDM) framework to assess obstacles and prioritize improvement strategies for loading and unloading operations at ports. The Fuzzy Best Worst Method (F-BWM) was applied to obtain consistent criterion weights, while Fuzzy MABAC was used to rank six strategic alternatives. Twenty-five operational sub-criteria, adapted and validated by experts, were used to reflect the port context. Results show that modernizing equipment combined with preventive maintenance is the strongest strategy across various sensitivity scenarios. This study contributes to the field by extending the application of hybrid MCDM to the port sector and by demonstrating how integrated methods enhance the weighting and ranking processes. From a managerial perspective, these findings provide structured decision support for port authorities to allocate resources effectively, prioritize technology-based interventions, and plan for long-term improvements in human resources and infrastructure.